The Effect of Resveratrol Supplementation on Cardio‐Metabolic Risk Factors in Patients with Type 2 Diabetes: A Randomized, Double‐Blind Controlled Trial. (1st September 2019) - Abdollahi, Shima; Salehi‐Abargouei, Amin; Toupchian, Omid; Sheikhha, Mohammad Hasan; Fallahzadeh, Hossein; Rahmanian, Masoud; Tabatabaie, Mahtab; Mozaffari‐Khosravi, Hassan
Abstract : The aim of the present randomized controlled trial was to evaluate the effect of a micronized resveratrol supplement on glycemic status, lipid profile, and body composition in patients with type 2 diabetes mellitus (T2DM). A total of 71 overweight patients with T2DM (body mass index ranged 25–30) were randomly assigned to receive 1000 mg/day trans‐resveratrol or placebo (methyl cellulose) for 8 weeks. Anthropometric indices and biochemical indices including lipid and glycemic profile were measured before and after the intervention. In adjusted model (age, sex, and baseline body mass index), resveratrol decreased fasting blood sugar (−7.97±13.6 mg/dL, p =0.05) and increased high density lipoprotein (3.62±8.75 mg/dL, p =0.01) levels compared with placebo. Moreover, the mean difference in insulin levels reached significance (−0.97±1.91, μIU/mL, p = 0.02). However, no significant differences were observed for anthropometric measures. It was found that 8‐week resveratrol supplementation produced useful effects on some cardio‐metabolic parameters in patients with T2DM. More studies are needed to confirm these findings.